The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1073/pnas.1100349108
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL28B gene variations with mathematical modeling of viral kinetics in chronic hepatitis C patients with IFN plus ribavirin therapy

Abstract: Asian patients with chronic hepatitis C (CHC) are known to have better virological responses to pegylated (Peg) IFN-based therapy than Western patients. Although IL28B gene polymorphisms may contribute to this difference, whether favorable hepatitis C virus (HCV) kinetics during treatment plays a role remains unclear. We enrolled 145 consecutive Taiwanese patients with CHC receiving Peg-IFN α-2a plus ribavirin for the study. Blood samples were taken more frequently at defined intervals in the first 3 d. Peg-IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 51 publications
(50 reference statements)
3
44
0
1
Order By: Relevance
“…We appreciate the comments of Guedj et al (1) on our paper addressing the association of IL28B gene variations with mathematical modeling of viral kinetics in patients with chronic hepatitis C treated with pegylated IFN plus ribavirin therapy (2). Regarding the distribution of the blips among hepatitis C virus (HCV) genotypes, we not only found a lower virion production rate but earlier blips among patients with HCV genotype 2 infection than those with genotype 1 infection.…”
mentioning
confidence: 63%
“…We appreciate the comments of Guedj et al (1) on our paper addressing the association of IL28B gene variations with mathematical modeling of viral kinetics in patients with chronic hepatitis C treated with pegylated IFN plus ribavirin therapy (2). Regarding the distribution of the blips among hepatitis C virus (HCV) genotypes, we not only found a lower virion production rate but earlier blips among patients with HCV genotype 2 infection than those with genotype 1 infection.…”
mentioning
confidence: 63%
“…In the absence of large studies with time scales of hours, it is difficult to verify if all the blips observed were generated by IFN/ribavirin therapy. Nonetheless, Hsu et al (1) showed that among patients who had blips, a significantly higher proportion of patients with SVR had early blips, suggesting that a large proportion of the blips were related to therapy. Because patients infected with HCV genotype 1 respond poorly to IFN/ ribavirin compared with those infected with HCV genotype 2, the distribution of the blips among HCV genotypes would be relevant.…”
mentioning
confidence: 99%
“…In PNAS, Hsu et al (1) observed an early transient increase (here, termed a blip) in hepatitis C virus (HCV) viral load in 92 out of 145 Taiwanese patients with chronic hepatitis C treated with pegylated IFN-α (IFN) and ribavirin and found that these blips were significantly associated with the outcome of therapy [i.e., sustained virologic response (SVR)]. Further, they sought to explain the origin and time of these blips using a version of a well-studied mathematical model of HCV infection and treatment (2) in a nonstandard way.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome-wide association studies (GWAS) have identified strong associations of single nucleotide polymorphisms (SNPs) in the interleukin-28B (IL28B) region with spontaneous clearance of HCV [22], therapeutic response, and early viral kinetics to combination therapy in HCV-infected individuals [23,24]. Since metabolic regulation and immune response are highly integrated [25], HCV-related immune reactions may play a given role in modulating the associations between serum Apo C-III and disease progression.…”
mentioning
confidence: 99%